First totally laparoscopic ALPPS procedure with selective hepatic artery clamping: Case report of a new technique. Issue 29 (July 2016) - Surjan, Rodrigo C.; Makdissi, Fabio F.; Basseres, Tiago; Leite, Denise; Charles, Luiz F.; Bezerra, Regis O.; Schadde, Erik; Machado, Marcel Autran
Abstract: Background: ALPPS (Associating Liver Partition and Portal vein ligation for Staged hepatectomy) is a new surgical approach for the treatment of liver tumors. It is indicated in cases where the future liver remnant is not sufficient to maintain postoperative liver function. We report a totally laparoscopic ALPPS with selective hepatic artery clamping. Pneumoperitoneum itself results in up to 53% of portal vein flow and selective hepatic artery clamping can reduce blood loss while maintaining hepatocellular function. Therefore, the combination of both techniques may result in effective control of bleeding with no damage in the liver function that may have direct impact in the result of ALPPS procedure. Methods: A 65-year-old man with colorectal liver metastases in all liver segments, except liver segment 1 (S1), were evaluated as unresectable. He underwent chemotherapy with objective response and multidisciplinary board decided for ALPPS procedure. First stage was performed entirely by laparoscopy and consisted of enucleation of metastases from segments 2 and 3, ligation of the right portal vein and liver splitting under selective common hepatic artery clamping. The second stage was done 3 weeks later and consisted of laparoscopic right trisectionectomy by laparoscopy. Results: Operative time was 250 and 200 minutes, respectively. Estimated blood loss was 150 and 100 mL. There was no need for transfusion or hospitalization in intensive care. He was discharged on the 3rd and 5th postoperative day, respectively. Recovery was uneventful after both stages and patient did not present any sign of liver failure. Elevation of liver enzymes was minimal. Computerized tomography (CT) scan before second stage showed a liver hypertrophy of 53%, sFLR was 0.37 before second stage, or 33% of the total liver volume. CT scan shows no residual liver disease and optimum liver regeneration. Patient is well with no evidence of the disease 11 months after the procedure. Conclusions: Totally laparoscopic ALPPS is a feasible and safe approach for selected patients with liver tumors. The hypertrophy of the remaining liver was adequate and sequential procedures were performed without morbidity and no mortality. Selective hepatic artery clamping seems to be an interesting solution to decrease intraoperative blood loss without the harsh effect of Pringle maneuver.